The Politics of Transnational Actors in Latin America - Shepherd, Frederick M., 1963- author.
1 online resource (186 pages
Keywords: The Politics of Transnational Actors in Latin America: Power from Afar explores the important issues of transnational actors and their influence on institutions and people in Latin America, raising profound questions of accountability, social justice, and sovereignty. The text focuses on four particularly significant groups that transcend national boundaries: the Catholic Church, transnational corporations, transnational drug networks, and transnational human rights networks. By comparing each of their impacts on the region, Frederick M. Shepherd explores larger questions about transnational power and how it has deeply penetrated the nations of Latin America. The book's analysis delves into attempts made over the last 100 years by citizens, social movements, and governments to reassert a degree of control over these transnational actors, setting up a framework to understand how local, national, and global forces interact in a setting of transnational dominance. The volume suggests that local and national groups can use principles and power to bring about equitable and just outcomes in relation to transnational actors, and that, in some cases, transnational actors can be a part of constructive change in Latin America. This concise volume will be of interest to students of History, Latin American and Caribbean Studies, and Political Science, as well as those interested in 20th-century Latin American politics and political history.